(3GdOQ GdefKhQ aj GdJaSjQ GdeCKhQ HGdeCKhQs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3gs
(3ChdgG (B:s
(3CNQL GdMGce hUMMg hGHf eQOhjg aj JaSjQg hCHh PQ GdgQhj aj aVd ecI hGdHjgbj aj GdTYH Yf eYbd Hf jSGQ bGd bGd QShd Gddg s
(3BNQgG (B:s
(3hCNQL Hf CHj TjHI Yf GdRgQj bGd dG EMUGQ EdG ef Nha hCNQL GHf CHj TjHI Yf YWGA bGd dG EMUGQ EdG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 /301s
(3eYLe GdeDdajf (B2 / 82s
(3cTa GdXfhf (B1 / 7 33s
(3TPQGJ GdPgH (B8 / 51s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs